UX DESIGN 2020 : the ultimate beginner's guide to user experience - Farrington, Theo, ....- (S.l. : Farrington, 2020)
The ultimate beginner's guide to user experience for everyone who wants to kickstart their career
Keywords: Gebruikersinterfaces; Web usability; Websites ontwerpen